2004
DOI: 10.1021/jo035584c
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies of the 13C NMR of Iodoalkynes in Lewis-Basic Solvents

Abstract: The (13)C NMR spectra of two different iodoalkynes, 1-iodo-1-hexyne (1) and diiodoethyne (2), exhibit a strong solvent dependence. Comparisons of the data with several common empirical models, including Gutmann's Donor numbers, Reichardt's E(N)(T), and Taft and Kamlet's beta and pi, demonstrate that this solvent effect arises from a specific acid-base interaction. Solvent basicity measures such as Donor numbers and beta values correlate well with the alpha-carbon chemical shift of 1, but polarity measures such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 29 publications
7
54
1
Order By: Relevance
“…The data acquired by Kochi et al suggests that the hydrogen bond donor ability of the solvent has a detrimental effect on halogen bonding, whereas environmental polarity possesses a considerably weaker and ambiguous influence. This conclusion is further supported by the observations of Goroff et al [23], who studied the interaction of 1-iodoalkynes with pyridine, quinolone, THF, acetone, benzophenone, and chloroform in a mixture with hexanes. Based on correlations of the 13 C NMR shifts to a variety of empirical models of solvent basicity, Goroff suggested that basicity plays an important role for the interaction strength, but not polarity.…”
Section: Neutral Two-center Halogen Bond Complexessupporting
confidence: 77%
“…The data acquired by Kochi et al suggests that the hydrogen bond donor ability of the solvent has a detrimental effect on halogen bonding, whereas environmental polarity possesses a considerably weaker and ambiguous influence. This conclusion is further supported by the observations of Goroff et al [23], who studied the interaction of 1-iodoalkynes with pyridine, quinolone, THF, acetone, benzophenone, and chloroform in a mixture with hexanes. Based on correlations of the 13 C NMR shifts to a variety of empirical models of solvent basicity, Goroff suggested that basicity plays an important role for the interaction strength, but not polarity.…”
Section: Neutral Two-center Halogen Bond Complexessupporting
confidence: 77%
“…According to these studies, the observed deshielding in MIF-1 would be consistent with coordination of the imidazole moiety to Zn 2 + ions, which, owing to differences in their coordination sphere, are slightly less strong Lewis acids than those in ZIF-8. [33][34][35] It has been pointed out previously that the chemical shifts and peak widths of the different carbon atoms of the surfactant are a sensitive probe of the conformation of the template confined in inorganic hosts and host-guest interfacial interactions. [36,37] The 13 C signals of all MIFs show a downfield shift of the inner-chain methylene and terminal carbon of the surfactant chain (C4-C15 and C16/17, for labeling see the scheme in Figure 4) by about 1-2 ppm with respect to that typically found for CTAB molecules occluded in hexagonal mesostructures, and are consistent with those found for lamellar mesostructures.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…[44] Additional support for this interpretation was obtained from good correlation with various empirical models of solvent basicity, including Gutmanns donor numbers and Taft and Kamlets b values. [45] Furthermore, poor correlation to Reichardts E N T values and Taft and Kamlets p* parameters suggests that solvent polarity does not play a role. [45] Interestingly, the resonance of the I-CA C H T U N G T R E N N U N G (sp 2 ) moiety of iodoarenes in 13 C NMR spectroscopic analysis does not undergo a downfield shift on changing from a noncoordinating to a coordinating solvent, even though complexation occurs.…”
Section: Introductionmentioning
confidence: 99%
“…[45] Furthermore, poor correlation to Reichardts E N T values and Taft and Kamlets p* parameters suggests that solvent polarity does not play a role. [45] Interestingly, the resonance of the I-CA C H T U N G T R E N N U N G (sp 2 ) moiety of iodoarenes in 13 C NMR spectroscopic analysis does not undergo a downfield shift on changing from a noncoordinating to a coordinating solvent, even though complexation occurs. [46] It was proposed that this phenomenon is because the nonrelativistic complexation shifts and the change in the spin-orbit-induced heavy-atom effect of iodine compensate each other.…”
Section: Introductionmentioning
confidence: 99%